Genially Digital Escape Rooms as a Micronearning Tool in the Context of a Trauma-Informed Approach - Zemlianska, Alina; Sharova, Tetiana; Legeza, Daria; Землянська, Аліна Вікторівна; Шарова, Тетяна Михайлівна; Легеза, Дар’я Георгіївна (Запоріжжя : ТДАТУ, 2026)
EN: The article substantiates the feasibility and effectiveness of the trauma-informed approach, the concept of microlearning and gamified digital technologies in the modern space of higher education in Ukraine. The essence of microlearning as a methodological system for managing human cognitive resources, based on the principles of granularity, temporal brevity, reducing mental load and personalization, is detailed. It is determined that the most relevant tool for the practical implementation of these principles is the Genially cloud platform, which provides multi-level interactivity, visual dynamics and wide possibilities for integrating multimedia content. As a practical case, the article presents the structure, functional features and experience of implementing the author's online educational quest “Rescue Mission: Solving the Pedagogical Crisis”, developed on the Genially platform within the framework of the international Erasmus+ SAFE LEARN project. /// UA: У статті обґрунтовано доцільність та ефективність травмоінформованого підходу, концепції мікронавчання (microlearning) та гейміфікованих цифрових технологій у сучасному просторі вищої освіти України. Деталізовано сутність мікронавчання як методологічно обґрунтованої системи управління когнітивними ресурсами людини, що базується на принципах гранулярності, часової лаконічності, зниження ментального навантаження та персоналізації. Визначено, що найбільш релевантним інструментом для практичної реалізації цих принципів є хмарна платформа Genially, яка забезпечує багаторівневу інтерактивність, візуальну динаміку та широкі можливості інтеграції мультимедійного контенту. Як практичний кейс у статті представлено структуру, функціональні особливості та досвід імплементації авторського навчального онлайн-квесту «Рятівна місія: вирішення педагогічної кризи», розробленого на платформі Genially в межах міжнародного проєкту Erasmus+ SAFE LEARN.
Цифрові квест-кімнати Genially як інструмент мікронавчання в контексті травмоінформованого підходу
Keywords: higher education; trauma-informed approach; microlearning; Genially; educational escape rooms; gamification; cognitive load; SAFE LEARN project; вища освіта; травмоінформований підхід; мікронавчання; освітні квест-кімнати; гейміфікація; когнітивне навантаження; проєкт SAFE LEARN